PRELIMINARY GEOMECHANICAL ANALYSIS ON LIMESTONES IN PPSDM GEOMINERBA CAMPUS, PADALARANG, WEST JAVA - Irvan Sophian; Herlinawati H; Nur Khairullah; Abdurrokhim A; Iyan Haryanto; Hendarmawan H (Puslitbang tekMIRA, 2019)
The research location is in the PPSDM Geominerba field campus. The campus is located in Padalarang, West Java that is surrounded by the open-pit mining of limestone and marble. This limestone was formed in Oligo-Miocene of Rajamandala Formation. The research objective was to determine the condition of the slopes around the campus based on geomechanical characteristics. Based on field observations, the slope angle in the area is dominated by steep slopes. The rock hardness level is dominated by hard rock with a hardness ranging from 50-100 MPa. Rock Mass Rating shows that the area is dominated by good rocks. While the Slope Mass Rating calculation show that the maximum slope angle is between 52-75°. Level of deformation and intensive weathering process will reduce the strength of the rock in the future. Several rock fall occurrences on this research area support this assumption. Yet, some local open pit mining area activity near the toe hill of the area need to be concerned regarding the effect of the local rock fall occurrences.